Characterization of Polybacterial versus Monobacterial Conjunctivitis Infections in Pediatric Subjects Across Multiple Studies and Microbiological Outcomes with Besifloxacin Ophthalmic Suspension 0.6% - Blondeau JM (Dove Medical Press, 2021)
Joseph M Blondeau,1 Howard M Proskin,2 Christine M Sanfilippo,3 Heleen H DeCory3 1Clinical Microbiology, Royal University Hospital, Saskatoon, SK, Canada; 2Howard M. Proskin & Associates, Rochester, NY, USA; 3Pharmaceutical Medical Affairs, Bausch + Lomb, Rochester, NY, USACorrespondence: Heleen H DeCoryPharmaceutical Medical Affairs, 1400 North Goodman Street, Rochester, NY, 14609, USATel +1 585 338-8161Email Heleen.DeCory@bausch.comIntroduction: The choice of empiric therapy for bacterial conjunctivitis should be guided by an awareness of typical causative pathogen distributions. Bacterial conjunctivitis can be polybacterial, although pediatric-specific data are lacking.Methods: This was a post-hoc analysis of data in pediatric subjects (1– 17 years) from five bacterial conjunctivitis trials evaluating besifloxacin ophthalmic solution 0.6%.Results: Of the 730 pediatric subjects with culture-confirmed conjunctivitis, nearly one-fourth (23.6%) had polybacterial infections and three-fourths (76.4%) had monobacterial infections at baseline. In both polybacterial and monobacterial infections, the most prevalent organisms were Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus aureus, and Streptococcus mitis/S. mitis group. In polybacterial versus monobacterial infections, S. mitis/S. mitis group (8.7% vs 4.3%; P=0.032) and Moraxella catarrhalis (4.7% vs 0.5%; P< 0.001) were identified more frequently, whereas S. pneumoniae (14.0% vs 28.1%; P< 0.001) was identified less frequently, as the dominant infecting species. MICs for individual species were similar for tested antibiotics regardless of polybacterial or monobacterial infection, except Staphylococcus epidermidis for which fluoroquinolone MICs were ≥ 3 dilutions higher for isolates of this species sourced from polybacterial compared to monobacterial infections. Treatment with besifloxacin resulted in microbial eradication in 79.1% of polybacterial and 92.3% of monobacterial infections (P≤ 0.005 vs vehicle).Discussion: One in four pediatric bacterial conjunctivitis infections is polybacterial, highlighting the need for a broad-spectrum antibiotic when choosing empiric therapy.Keywords: pediatric, conjunctivitis, polybacterial, besifloxacin, minimum inhibitory concentration